Conspecific females promote calling behavior in the noctuid moth, Pseudaletia adultera. Issue 3 (8th June 2016) - Rehermann, Guillermo; Altesor, Paula; McNeil, Jeremy N.; González, Andrés
Abstract: Changes in female calling behavior in response to the presence of conspecific pheromones (pheromone autodetection) have been demonstrated in a number of moth species. However, the observed changes vary between species, and several ecological and adaptive explanations for autodetection have been proposed. We studied the effect of conspecific females on the calling behavior of the noctuid moth Pseudaletia adultera (Schaus) (Lepidoptera: Noctuidae, Hadenini), by comparing the age of first calling, as well as the onset and pattern of calling, when females were held individually or in the presence of conspecifics. Grouped females started calling at a lower age, a higher percentage of females called during the scotophase, and they called longer compared to females held in isolation. We also demonstrated that female antennae respond to each of the three main components of the sex pheromone – ( Z )‐11‐hexadecen‐1‐ol, ( Z )‐11‐hexadecen‐1‐yl acetate, and ( Z )‐11‐hexadecenal – and that the response patterns differed from those of male antennae. By calling more and extending her calling window in presence of conspecific females, a female may increase her chances of accessing males. However, the potential benefits need to be considered within an ecological context, considering factors such as migration, oviposition, and foraging.